Developmental Plasticity of the Amphibious Liverwort Riccia fluitans - Althoff, Felix; Wegner, Linus; Ehlers, Katrin; Buschmann, Henrik; Zachgo, Sabine (Frontiers in Plant Science, 2022)
The colonization of land by ancestors of embryophyte plants was one of the most significant evolutionary events in the history of life on earth. The lack of a buffering aquatic environment necessitated adaptations for coping with novel abiotic challenges, such as high light intensities and desiccation as well as the formation of novel anchoring structures. Bryophytes mark the transition from freshwater to terrestrial habitats and form adaptive features such as rhizoids for soil contact and water uptake, devices for gas exchange along with protective and repellent surface layers. The amphibious liverwort Riccia fluitans can grow as a land form (LF) or water form (WF) and was employed to analyze these critical traits in two different habitats. A combination of light microscopy, SEM and TEM studies was conducted to characterize and compare WF and LF morphologies. A complete phenotypic adaptation of a WF plant to a terrestrial habitat is accomplished within 15 days after the transition. Stable transgenic R. fluitans lines expressing GFP-TUBULIN and mCherry proteins were generated to study cell division and differentiation processes and revealed a higher cell division activity in enlarged meristematic regions at LF apical notches. Morphological studies demonstrated that the R. fluitans WF initiates air pore formation. However, these pores are arrested at an early four cell stage and do not develop further into open pores that could mediate gas exchange. Similarly, also arrested rhizoid initial cells are formed in the WF which exhibit a distinctive morphology compared to other ventral epidermal cells. Furthermore, we detected that the LF thallus has a reduced surface permeability compared to the WF, likely mediated by formation of thicker LF cell walls and a distinct cuticle compared to the WF. Our R. fluitans developmental plasticity studies can serve as a basis to further investigate in a single genotype the molecular mechanisms of adaptations essential for plants during the conquest of land.